Caves, Karst Features and Speleological Heritage in Chapada Diamantina, Bahia, Brazil - Parra, Raphael; Pereira, Ricardo Galeno Fraga de Araujo; da Purificação, Carlos Gleidson Campos (Revista Brasileira de Geomorfologia, 2023)
Chapada Diamantina is among the best known and most visited landscapes in Brazil. Located in the state of Bahia, Northeast region of the country, it is characterized by mountains and plateaus that developed on Proterozoic sedimentary and metasedimentary rocks. Much of its territory is covered by carbonate and siliciclastic rocks, where relevant karst systems develop, marked by the occurrence of sinking streams, sinkholes, and caves with a great diversity of morphologies, speleothems, subterranean fauna, and paleontological and archaeological records. Relevant carbonate systems occur in Iraquara, such as the Lapa Doce, Torrinha, and Pratinha caves, which represent important tourist attractions. Also in these rocks, stand out the Brejões Cave, with a 106-m high entrance, and the Toca da Boa Vista, the largest cave in South America, extending across 114 km. Cultural manifestations are present in the prehistoric cave paintings at Santa Marta Shelter and recent religious pilgrimages at Mangabeiras Cave, in Ituaçu. In turn, siliciclastic karst systems are mainly in Serra do Sincorá. The Lapão and Castelo caves have expressive speleogens and speleothems, as well as the Torras Cave, in the Igatu region, ranked as the second largest in Brazil considering siliciclastic rocks.